Pengaruh Lokasi, Kualitas Pelayanan, Dan Fasilitas Terhadap Kepuasan Wisatawan Pada Goa Rangko Labuan Bajo, Kecamatan Boleng, Kabupaten Manggarai Barat - Yuliana Alexia Idar; Made Setena; Ida Ayu Agung Idawati (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2024)
The purpose of this study is to ascertain how Rangko Cave in Labuan Bajo is affected by its location, level of service, and amenities. This place is in the West Manggarai Regency's Rangko Labuan Bajo Cave in the Komodo District. The population uses tourists, with a sample size of 100 people and a total of 17,361 visitors to Rangko Cave in 2022. Some of the methods used to look at data are the validity, reliability, classical assumption, multiple linear regression, coefficient of determination, F, and t tests. Researchers have found that both location and the quality of services and facilities have a good and significant effect on how happy visitors are. Location also has a big and good effect on how happy visitors are. Lastly, facilities have a big and good effect on how happy visitors are. Researchers can make ideas that should be carried out by the company. For example, they could offer good service, make sure there are enough facilities, and ask customers for feedback to get tourists wanting to come back to Rangko Cave, Labuan Bajo. Then it would be better for the company to place one person on the road to regulate traffic, place tourist attraction signboards, carry out supervision, carry out routine evaluations, provide special training to officers on effective communication skills and provide adequate changing rooms for visiting tourists.